2018
DOI: 10.1007/s00787-018-1194-0
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms at 13 years as predictors of depression in older adolescents: a prospective 4-year follow-up study in a nonclinical population

Abstract: Depression is the most important source of disability in adolescents, partially due to its recurrence. There is a lack of studies on population-based samples investigating the continuity of depressive symptoms during adolescence. This study evaluates depressive symptoms at early adolescence as predictors of depressive symptoms later in adolescence. Urban adolescents born in 1990 and enrolled in schools of Porto, Portugal, in 2003-2004 (EPITeen study) were evaluated at 13 and 17 years (n = 1106, 55.9% females),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
1
1
Order By: Relevance
“…In the current study, the prevalence of adolescents with mild to severe depressive symptoms was 15%, higher than the frequency observed in another Portuguese study [61], which reported 11.9% among adolescents with the same age. In addition, we found that adolescents with higher scores on BDI-II had higher odds of belonging to the "Picky eating" and, especially, "Emotional eating" and "Food attractiveness" patterns.…”
Section: Discussioncontrasting
confidence: 87%
“…In the current study, the prevalence of adolescents with mild to severe depressive symptoms was 15%, higher than the frequency observed in another Portuguese study [61], which reported 11.9% among adolescents with the same age. In addition, we found that adolescents with higher scores on BDI-II had higher odds of belonging to the "Picky eating" and, especially, "Emotional eating" and "Food attractiveness" patterns.…”
Section: Discussioncontrasting
confidence: 87%
“…Por otro lado, la prevalencia global de depresión en los estudiantes fue del 62 % de ellos el 35,4 % tuvieron depresión leve, siendo el sexo femenino el más afectado (52,9 %) vs el sexo masculino (47,1 %), prevalencia menor a la reportada en adolescentes de 16 a 17 años de Túnez, cuya tasa fue del 75,9 % y superior a investigaciones internacionales realizadas en estudiantes de secundaria y universitarios de 13 a 23 años en Tailandia, China, Portugal, Brasil, Estados Unidos, México y Chile, donde se encontró valores entre el 1,06 % y 28,8 % (28,(42)(43)(44)(45)(46). A nivel nacional estudios previos realizados en Quito, Guayaquil, Cuenca y Zamora reportaron prevalencias menores entre el 14,8 % y 40,2 % (6, 35,[47][48][49].…”
Section: Artículo Originalunclassified
“…The persistence and exacerbation of depressive symptoms is not only an important symptomatic criterion for the diagnosis of depression ( 14 ), but these symptoms are important causes of deterioration in physical health ( 15 , 16 ), impact on immune function ( 17 , 18 ), increasing the risk of chronic disease ( 19 , 20 ), and self-injurious suicidal behavior ( 21 , 22 ). There is a long-term and complex relationship between depressive symptoms, mortality risk, and life expectancy ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%